Analisis Implementasi E-Budgeting Menggunakan Model CIPP (Context, Input, Process, And Product) Serta Dampaknya Terhadap Transparansi Dan Akuntabilitas Keuangan Publik Di SKPD Kabupaten Karangasem - Ni Ketut Erna Kartika Lestari; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The research was aimed to analyse the role of e-budgeting system application by using CIPP model, and its impact on the transperancy and accountability of public finance on SKPD in Karangasem regency. The research was done in Karangasem regency of Bali Province, by taking eight Skpd samples from all of skpd in karangasem regency. Those samples were Department for environnent, department of agriculture, department of education youth and sport, department of public works, department of Koperasi, chief of Bebandem district, and chief of Karangasem district. As for the conclusion of the research was the implementation of e-budgeting system on SKPD in Karangasen regency reviewed through CIPP model could give significant benefits in public finance management, so that the goal of this system implementation can be reached as much as possible. The implementation of e-budgeting system gave impact to transperancy and accountability on skpd in karangasem regency, though the level of transperancy and accountability of public finance management has not yet running optimally, because of the factor of society's role which has not yet played well.